جماليــــــات الفاصلــــــة القرآنيـــــــة (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص :      جمال القرآن جمال متفرد، لا يماثله جمال أو يقترب منه، والفاصلة القرآنية لوحة جمالية  من جمالياته وركيزة بيانية في نظمه، وركن بارز في تركيبه، تضفي عليه جمالاً وإعجازاً، والمتذوق للغة الخطاب القرآني، يدرك مكانة الفاصلة القرآنية وموقعها وهدفها من حيث دلالة المعنى ودلالة الإيقاع معًا، فهي تخلب اللب، وتأخذ بالإحساس، وتمتلك النفس، شديدة الارتباط بالمعنى، واختلاف الفواصل يفضي إلى اختلاف المعاني، وتكرارها بلفظ واحد فيه تأكيد ومبالغة، فهي قيمةٌ جمالية صوتيةٌ، لها وظيفةٌ مهمةٌ بما تحمله من إيحاءات ومعان، يراعى فيها اللفظ والجرس والدلالة.الكلمات الدالة: الخطاب القرآني - الفاصلة القرآنية – جماليات   Abstract: The  beauty  of Quran  is  unique. No beauty is similar  or close to it The koranic comma  is one of its painting   aesthetics  and  a graphic anchor  of its composition. It gives  Quran  beauty  and miracle. The connoisseur  of the language  of the Quran discourse  understands the status  ,location and  aim of the koranic  comma  in terms  meaning and  rythm  together. It exudes  the pulp ,takes  the feeling  and possesses  the soul .It is closely  related  to the meaning and different different  separations  add  different  meanings  .Its repetition  in one word  has affirmation  and exageration. It is an aesthetic  and acoustic  value. It has  an important function  including references  and meanings,taking  into  account the  prononciation,intonation  and  significance. Keywords: Aesthetisc -  Quranic discourse - Quranic comma